Os processos educativos no trabalho de coleta e separação de resíduos sólidos na cidade de Pelotas/RS - Gotardo, Solaine (2011)
This paper broaches the educational processes concerned to the work of solid waste selective collection using as reference the dynamic of production, both associated and single. First we present the research outlines pointing the origins of the proposal, its methodological course and the data obtained through the cooperative field analysis. Subsequently we part from the theoretical referential to discuss the work dimensions in collecting and separating solid waste, relating them to the aspects of the research street field. In the third part we aim to approach the theoretical framework and the previous information between the collectors work in cooperatives and in the streets, emphasizing the perspective of the formation of a Labour Pedagogy. Finally we present some results of the research which allow us to conclude that as a learning process, the work of collecting on the streets is restricted to a mechanical reproduction of work as a way of living, without an implicit pedagogical perception. The impact on the achievement of this activity is in the fact that the workers don t recognize their learning process and remain isolated from the other workers, who are understood as contestants and not as partners. This atomization grants a guardianship relation under their buyers, who are the people which guarantee for the informal collectors in the streets a source of information and preparation for work In their turn the pedagogical processes in solidarity enterprises are more intensely experienced under the aspects of organization, management and relationship among the workers and the impact produced at work, according to the associated form, is in the fulfilment of a self-managed activity under a less painful condition to the labour fullfilment